Physiological and Physical Profile of Snowboarding: A Preliminary Review - Vernillo, Gianluca; Pisoni, Cesare; Thiébat, Gabriele (Frontiers in Physiology, 2018)
The sport of snowboarding has grown in popularity as both a recreational winter activity as well as a prominent Olympic sport. Both forms are comprised of one of three different disciplines within the sport: freestyle, alpine, and snowboard-cross. In recent years, the increased professionalism and substantial growth of snowboarding as a global sport has increasingly attracted the interest of exercise physiologists and sport scientists. Given the small (but growing) number of studies that have been published, the research analyzing the physiological and performance characteristics and requirements of snowboarding remains limited. The absence of such studies signifies a lack of examination into this important but under-explored area of research, which could contribute valuable information to the scientific community and international snowboarding teams. The studies conducted thus far have indicated different requirements of physiological and physical traits dependent upon the specific discipline of snowboarding in question. For example, in order to meet the divers demands of each discipline, athletes must develop various qualities, such as muscular strength and power. This can increase their ability to withstand the high forces and loads on the muscular system during competition, and further decrease their risk of lower limbs injuries. At the same time, the studies acknowledge the potential advantages of aerobic fitness in terms of recovery, to more efficiently sustain the athlete through both competitive and on- and off-snow training sessions. Given the value and breadth of application of these limited studies, further analysis and research could contribute greater knowledge and benefits to the field of snowboarding. Therefore, it is the purpose of this preliminary review to explore the current literature, providing further insight into the physiological and physical demands of snowboarding performance. This preliminary review is intended to stimulate interest among the communities of exercise physiologists, sport scientists and particularly coaches in order to improve our current understanding of snowboarding and its demands as a sport. This preliminary review further seeks to develop protocols and strategies to assess physiological and performance characteristics of snowboarding, monitor athletic performance, provide practical recommendations for training, identify new areas of scientific research, and develop accurate talent identification programs.